ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS PENGISIAN REKAM MEDIS OLEH TENAGA KESEHATAN DI RSUD AROSUKA SOLOK - Dian Sari; Maisharoh Maisharoh (Ensiklopedia Research and Community Service Review, 2026)
The quality of inpatient medical record filling is still an important problem in hospitals because it affects the continuity of Service, legal aspects, and accreditation. In RSUD Arosuka Solok, found incompleteness of filling several components of medical records such as Patient Identity, progress records, and signatures of health workers. This study aims to analyze the quality of inpatient medical record filling and related factors. This study uses quantitative type with cross-sectional design. The location of the study in Arosuka Solok hospital with a sample of 120 inpatient medical record files were selected using systematic random sampling technique. Data collection was conducted through observation using a checklist sheet according to the Ministry of Health Standards. Data analysis include univariate for frequency distribution and bivariate using chi-square test with significance level 0.05. The univariate results showed that 65.8% of medical records were incomplete, with the highest incompleteness in the progression record (54.2%) and the doctor's signature (47.5%). Bivariate analysis showed a significant relationship between the workload of health workers (p=0.003), the level of knowledge of officers (p=0.001), and supervision (p=0.005) with the quality of filling medical records. The conclusion of this study is that the quality of filling in medical records at AROSUKA Solok hospital is still not optimal and is influenced by individual and organizational factors. Keywords: Recordingmedical; Quality; Rawatinap; Completeness; Supervision